Transmembrane signal transduction by cofactor transport. Issue 37 (20th August 2021) - Kocsis, Istvan; Ding, Yudi; Williams, Nicholas H.; Hunter, Christopher A.
Abstract : Synthetic transducers transport externally added metal ion cofactors across the lipid bilayer membrane of vesicles to trigger catalysis of ester hydrolysis in the inner compartment. Signal transduction activity is modulated by hydrazone formation. Abstract : Information processing and cell signalling in biological systems relies on passing chemical signals across lipid bilayer membranes, but examples of synthetic systems that can achieve this process are rare. A synthetic transducer has been developed that triggers catalytic hydrolysis of an ester substrate inside lipid vesicles in response to addition of metal ions to the external vesicle solution. The output signal generated in the internal compartment of the vesicles is produced by binding of a metal ion cofactor to a head group on the transducer to form a catalytically competent complex. The mechanism of signal transduction is based on transport of the metal ion cofactor across the bilayer by the transducer, and the system can be reversibly switched between on and off states by adding cadmium(ii ) and ethylene diamine tetracarboxylic acid input signals respectively. The transducer is also equipped with a hydrazide moiety, which allows modulation of activity through covalent conjugation with aldehydes. Conjugation with a sugar derivative abolished activity, because the resulting hydrazone is too polar to cross the bilayer, whereas conjugation with a pyridine derivative increased activity. Coupling transport with catalysis provides a straightforward mechanism for generating complex systems using simple components.